Developmental differences in brain functional connectivity during social interaction in middle childhood. (April 2022) - Xiao, Yaqiong; Alkire, Diana; Moraczewski, Dustin; Redcay, Elizabeth
Abstract: The transition from childhood to adolescence is marked by significant changes in peer interactions. However, limited research has examined the brain systems (e.g., mentalizing and reward networks) involved in direct peer interaction, particularly during childhood and early adolescence. Here, we analyzed fMRI data from 50 children aged 8–12 years while they participated in a task in which they chatted with a peer (Peer) or answered questions about a story character (Character). Using a beta-series correlation analysis, we investigated how social interaction modulates functional connectivity within and between mentalizing and reward networks and whether this modulation changes with age. We observed effects of social interaction on functional connectivity were modulated by age within the mentalizing and reward networks. Further, greater connectivity within and between these networks during social interaction was related to faster reaction time to the Peer versus Character condition. Similar effects were found in the salience and mirror neuron networks. These findings provide insights into age-related differences in how the brain supports social interaction, and thus have the potential to advance our understanding of core social difficulties in social-communicative disorders, such as autism spectrum disorder. Highlights: We examined brain functional connectivity in a social-interactive context. The effect of social partner on mentalizing and reward networks was modulated by age. Connectivity within and between these networks is related to behavioral performance. These effects are also found in salience and mirror neuron networks.